UNIQUE ANIMATION VIDEO THREAT AGAINST STATE (VANASONIK ATERA) BASED MULTIMEDIA FOR THE STUDENT CLASS X SENIOR HIGH SCHOOL - Kholil Dwi Irawati; Minto Santoso; Ida Putri Rarasati (Universitas Islam Balitar, 2019)
This research aims to find out how the development of unique multimedia-based video animation media and also to find out how to use the animation media. The method used by the Research and Development method (research and development). The subjects involved in this research were 3 media experts, 3 material experts and 3 linguists and students of Nabawi Maftahul Uluum High School class X IPS 1. The experts gave an assessment of the feasibility of the product while the students gave responses to the products developed. The results of the research are the products developed are very feasible based on expert validation, ie material experts get an average percentage of 91.42%, media experts at 88.8% and linguists at 90.6%, the products developed are also interesting based on student responses with the acquisition of an average percentage of 84.4%, while the results of the product use step test, before the use step was not yet appropriate but after being tested and observed the improved use steps became appropriate and appropriate for use in video learning , expected that with the presence of media this learning can be more fun and actively involve students